2021
DOI: 10.1007/s10278-020-00417-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung Nodule Classification Using Biomarkers, Volumetric Radiomics, and 3D CNNs

Abstract: We present a hybrid algorithm to estimate lung nodule malignancy that combines imaging biomarkers from Radiologist’s annotation with image classification of CT scans. Our algorithm employs a 3D Convolutional Neural Network (CNN) as well as a Random Forest in order to combine CT imagery with biomarker annotation and volumetric radiomic features. We analyze and compare the performance of the algorithm using only imagery, only biomarkers, combined imagery + biomarkers, combined imagery + volumetric radiomic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…The difference between 3D MRA‐CapsNet‐DL_B and the best SVM fusion model is only 0.73%. Compared with some binary classification methods in literatures, 39–42 although our results are partially suboptimal, our performed four‐classification task is more difficult than the binary classification tasks. In addition, the constructed aided diagnosis model does not need to design and extract traditional manual features, nor does it use additional supplementary information such as serum biomarkers, and it can achieve good and stable performance in the classification of multiple pathological types of pulmonary nodules by only using CT image information.…”
Section: Experiments and Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The difference between 3D MRA‐CapsNet‐DL_B and the best SVM fusion model is only 0.73%. Compared with some binary classification methods in literatures, 39–42 although our results are partially suboptimal, our performed four‐classification task is more difficult than the binary classification tasks. In addition, the constructed aided diagnosis model does not need to design and extract traditional manual features, nor does it use additional supplementary information such as serum biomarkers, and it can achieve good and stable performance in the classification of multiple pathological types of pulmonary nodules by only using CT image information.…”
Section: Experiments and Resultsmentioning
confidence: 73%
“…In order to more comprehensively verify the classification performance of the constructed 3D MRA‐CapsNet‐DL aided diagnosis model, we compared the 3D MRA‐CapsNet‐DL model with six multi‐modal fusion models 16,17,39–42 . The comparison results are shown in Table 6.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early works on convolutional neural networks (CNNs) compared to computer-aided detection/diagnosis (CAD) demonstrated a superiority of the radiomic approach in nodule classification, with a decrease in false positives, possibly reducing the need of several follow-ups [ 19 , 20 , 21 ]. Mehta et al combined biomarkers, volumetric radiomics, and 3D CNNs to reach an algorithm classifying lung nodules [ 22 ]. Concerning histological subtyping, numerous studies have demonstrated the correlation between radiomic features and histology.…”
Section: The Role Of Radiomics In Lung Diseasesmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related death in many countries, and the accurate histopathological diagnosis is of great importance in subsequent treatment [11,12]. In previous studies, the RF model was mostly applied to detecting lung cancer, the classifcation of benign and malignant pulmonary nodules, and the analysis of lung cancer prognosis [13][14][15][16]. However, for therapeutic purposes, primary lung cancers fall into three major subtypes: lung adenocarcinoma (ADC), lung squamous cell carcinoma (SCC), and small cell lung cancer (SCLC), and distinguishing among subtypes is still particularly challenging.…”
Section: Introductionmentioning
confidence: 99%